E-professionalism in medical sciences: A hybrid concept analysis - Leili Mosalanejad; Mansoor Tafvisi; Nahid Zarifsanaiey (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Professionalism is one of the most important and vital concepts in the medical sciences. With the rapid growth of e-learning in the medical sciences in the past few years, the concept of virtual professionalism has emerged. This study was conducted as a hybrid concept analysis on describing e-professionalism in medical sciences. MATERIALS AND METHODS: This is a qualitative study with a hybrid concept analysis approach, consisting of theoretical stage, field research, and analysis. In the theoretical stage, the concepts of e-professionalism in medical sciences were identified through a review of the literature. During the fieldwork stage, in-depth interviews were conducted with five medical students who were intentionally selected. Finally, after analyzing the literature and the qualitative interviews, a theoretical description of e-professionalism concept in the field of medical sciences was extracted. RESULTS: the themes (3 numbers) and the subthemes (4 numbers) were extracted from 62 codes. These themes include information and communion technology and educational strategies professionalism in medical education. CONCLUSIONS: For describing professionalism, it is necessary to consider education and culture, role models, by emphasizing on the acceptance of professional responsibility, developing and improving social media policies, determining the scope of communication and interaction between individuals, and identifying the boundary between local laws and customs.